Physiological and molecular biomarkers of environmental contaminant-associated immunotoxicity in harbour seals (Phoca vitulina) - Mos, Elisabeth (2006)
Persistent organic pollutants (POPs) have been contaminating the marine environment since the mid 2Oth Century and continue to do so today. The polychlorinated biphenyls (PCBs) are of particular concern, since they are found at high concentrations in marine mammals throughout the Northern Hemisphere, and have been associated with endocrine disruption, reproductive impairment, immunotoxicity, and outbreaks of disease. In this study, samples were obtained from free-ranging harbour seal (Phoca vituilna) pups, which were live-captured in British Columbia, Canada, and Washington State, USA, in order to assess adverse health effects associated with POPs on the immune system of these mammals. PCBs were the most abundant of the 31 POPs measured in seals, and represented the greatest toxicological concern on the basis of established reference values for laboratory rodents and aquatic wildlife consumers. Seal immune function was assessed using traditional measures of immunotoxicity, including hematology, innate immune function, and adaptive immune function, and related to PCB concentrations while carefully controlling for confounding factors such as age, sex and condition. PCB concentrations negatively correlated to phagocytosis, T lymphocyte proliferative responses, (thymosin-a1-induced) lymphocyte signalling, and lymphocyte counts, and positively associated with the respiratory burst of phagocytes and aryl hydrocarbon receptor (AhR) expression of white blood cells, suggesting chemical-associated immunotoxicity. Parallel experiments, in which harbour seal white blood cells were exposed in vitro to 2,3,7,8-tetrachlorodibenzo-p-dioxin, a potent immunotoxicant, further supported the hypothesis that the observed reduction in immunocompetence in free-ranging seals may be due to an AhR-mediated mechanism of immunotoxicity. Principal component analysis (PCA) of immunological endpoints combined evidence of PCB-associated effects on the immune system as a whole. However, PCA also identified a difference between the immunological ...